Dukungan Keluarga dengan Tingkat Kecemasan pada Klien Komplikasi Mikrovaskuler di Blud RSUD dr. Doris Sylvanus Palangka Raya - Natalansyah Natalansyah; Dewi Fitriyani; Reny Sulistyowati (Jurnal Forum Kesehatan : Media Publikasi Kesehatan Ilmiah, 2020)
Microvascular complications including damage to the eye (retinopathy) causing blindness, for the kidneys (nephropathy) causing kidney and nerve failure (neuropathy) which causes impotence and diabetic foot disorders (including severe infections leading to amputations). Family support is needed to provide comfort physical and psychological state when experiencing pain. Family support is very important for the survival of people with DM, so with good family support, the level of anxiety felt by the client will be reduced. The method in this study is a quantitative method with a cross sectional design approach using a simple Multinomial Regression Test. The sampling technique used was purposive sampling. The sample used as many as 40 respondents who are clients with DM complications. The results of this study were most age variables were in the range of age 46-65 years as much as 57.5%, sex variables were mostly female sex as much as 52.5%, the highest education level variables were Higher Education (SMA-PT) as many as 55%, the highest occupational status variable is 57.5% of respondents who do not work, the highest economic status variable is the respondent earning <Rp. 1,000,000 as much as 40%, the old variable suffering from DM is 1-5 years as much as 62.5% and the family variable is the most caring treated by his wife and children 32.5%. Family support in Dr..Doris Sylvanus Palangka Raya Hospital good category as much as 47.5% and mild anxiety level as much as 15 37.5%. There is a relationship between family support and client anxiety level with microvascular complications (p = 0,000).